Analisis Motivasi Belajar Peserta Didik melalui Pemberian Layanan Informasi di SDN 12 VII Koto Sungai Sarik - Syahri, Lia Mita; Arafani, Adnan; Abdurrahman, Faris (Lembaga Yasin AlSys, 2025)
The success in the educational process is influenced by the willingness of students to carry out their duties while studying, the willingness of students in undergoing their education, encouragement / motivation is needed for these students, starting from motivation within themselves and motivation from outside the students. This study aims to analysis the state of student learning motivation, after obtaining information services conducted by students of the Master Program in Guidance and Counseling, Faculty of Education, State University of Padang at SDN 12 VII Koto Sungai Sarik. This research uses descriptive quantitative research. This study also used an instrument in the form of a learning motivation questionnaire using a guttman scale which has a weighted answer score of Yes = 2; No = 1. From this study the results obtained 1) There are 14 students who have a level of learning motivation with a percentage of 73.68%; 2) There are 5 students who have a learning motivation level with a percentage of 26.32%; 3) There are no students whose learning motivation is in the medium, low, and very low categories. Therefore, it can be seen that the level of learning motivation of students at SDN 12 VII Koto Sungai Sarik, after receiving information services, the average learning motivation is in the high category.